Differences in Alpha Diversity of Gut Microbiota in Neurological Diseases - Li, Zhuoxin; Zhou, Jie; Liang, Hao; Ye, Li; Lan, Liuyan; Lu, Fang; Wang, Qing; Lei, Ting; Yang, Xiping; Cui, Ping; Huang, Jiegang (Frontiers in Neuroscience, 2022)
Background: Neurological diseases are difficult to diagnose in time, and there is presently a lack of effective prediction methods. Previous studies have indicated that a variety of neurological diseases cause changes in the gut microbiome. Alpha diversity is a major indicator to describe the diversity of the gut microbiome. Currently, the relationship between neurological diseases and the alpha diversity of the gut microbiome remains unclear. Methods: We performed a systematic literature search of Pubmed and Bioproject databases up to January 2021. Six indices were used to measure alpha diversity, including community richness (observed species, Chao1, and ACE), community diversity (Shannon, Simpson), and phylogenetic diversity (PD). Random-effects meta-analyses on the standardized mean difference (SMD) were carried out on the alpha diversity indices. To explore the sources of interstudy heterogeneity, subgroup analyses were performed. Meta-analysis was performed on articles matching the age, sex, and body mass index of the disease group and the control group. Meanwhile, the subgroup analysis controlled for sequencing region, platform, geographical region, instrument, and diseases. Results: We conducted a meta-analysis of twenty-four published studies on 16S rRNA gene amplified sequencing of the gut microbiome and neurological diseases from the Pubmed and Bioproject database (patients, n = 1469; controls, n = 1289). The pooled estimate demonstrated no significant difference in the alpha diversity between patients and controls (P  0.05). Alpha diversity decreased only in Parkinson's disease patients, while it increased in anorexia nervosa patients compared to controls. After adjusting for age, sex, body mass index, and geographical region, none of the alpha diversity was associated with neurological diseases. In terms of Illumina HiSeq 2000 and the V3-V5 sequencing region, the results showed that alpha diversity increased significantly in comparison with the controls, while it decreased in Illumina HiSeq 2500. Conclusions: Our review summarized the relationship between neurological diseases and the alpha diversity of the gut microbiome. Perturbations of the alpha diversity are associated with Parkinson's disease and anorexia nervosa. Alpha diversity may not be a biomarker for the occurrence and development of neurological disease.